VARIATIONS IN 129I/127I RATIOS IN RECENT MARINE SEDIMENTS: EVIDENCE FOR A FOSSIL ORGANIC COMPONENT - Moran J.E.; Fehn U.; Teng R.T.D. (My University, 1998)
The value of the pre-bomb 129I/127I ratio in the hydrosphere is important for the use of this isotope system for dating and tracing purposes. In order to determine this value and to examine spatial variability, 129I/127I ratios were measured in 25 sediment samples from five cores taken at geographically distinct coastal areas. The results indicate a pre-anthropogenic 129I/127I ratio of 1500x10-15, in good agreement with values derived from previous sediment and groundwater studies. Results from shallow sediments show that the layer of bioturbation is dominated by the addition of anthropogenic 129I. The good agreement between results for this layer from different cores supports the understanding that marine iodine is isotopically homogeneous and associated with organic material which is actively remineralized at the sediment-water interface. Lower ratios (down to 354x10-15, corresponding to an age of 32.5 Ma) and larger variations than expected were found in sections of the cores below the layer of bioturbation. These observations can be explained by the presence of refractory fossil organic material, transported by rivers to the sediments from uplifted, continental shales. The results suggest that marine iodine is present in two forms, a labile component which is isotopically homogeneous, and a refractory component which is associated with kerogen (or other fossil organic compounds) whose 129I/127I ratio reflects the age of these compounds. 129I/127I ratios can be used to identify and date fossil organic material in Recent sediments, the presence of which can alter the assumptions underlying models of the global carbon cycle.
Keywords: MARINE SEDIMENTS; FOSSIL ORGANIC COMPONENT; HYDROSPHERE; KEROGEN; GLOBAL CARBON CYCLE